1991
DOI: 10.1161/01.res.69.5.1293
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with polyethylene-glycolated superoxide dismutase partially restores endothelium-dependent vascular relaxations in cholesterol-fed rabbits.

Abstract: The endothelium-derived relaxing factor is rapidly inactivated by superoxide radicals, and atherosclerotic vessels generate excess radical species. We tested the hypothesis that an imbalance between intrinsic superoxide dismutase (SOD) activity and the generation of superoxide radicals in atherosclerotic arteries may result in augmented inactivation of endothelium-derived relaxing factor. Vascular SOD was increased in normal and cholesterol-fed (1% cholesterol for 4 months) rabbits approximately twofold by tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
145
0
5

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(166 citation statements)
references
References 29 publications
16
145
0
5
Order By: Relevance
“…This condition would then inhibit the ultrastructural changes of aorta thus prevent the development of atherosclerotic lesion as shown in our study. The present study has shown that disrupted aortic ultrastructure has been improved in this finding, in line with previous study that showed endothelium injury impairment by ROS could be restored by antioxidants (Mugge et al, 1991). …”
Section: Electron Microscopic Observationsupporting
confidence: 93%
“…This condition would then inhibit the ultrastructural changes of aorta thus prevent the development of atherosclerotic lesion as shown in our study. The present study has shown that disrupted aortic ultrastructure has been improved in this finding, in line with previous study that showed endothelium injury impairment by ROS could be restored by antioxidants (Mugge et al, 1991). …”
Section: Electron Microscopic Observationsupporting
confidence: 93%
“…Peroxynitrite may contribute to the pathogenesis of atherosclerosis by modifying LDL directly, as well as shown here by releasing copper from caeruloplasmin, which would then promote lipid peroxidation [17-l 91. Whether peroxynitrite is formed in the vasculature is still unclear, although indirect evidence supports the hypothesis that superoxide and nitric oxide are formed simultaneously in atherosclerotic lesions [20,21]. This study supports the idea that caeruloplasmin is a likely source of the redoxactive copper recently detected in atherosclerotic postmortem material [22], and this may have arisen as a consequence of direct damage by peroxynitrite.…”
Section: Freshly Taken Plasma (Heparinised) From Three Normalsupporting
confidence: 81%
“…Additionally, hyperglycemia increases the production of ROS, of which SO Development 131 (10) Research article is known to combine with NO and deplete it from the system, thus inhibiting NO mediated intracellular signaling and downstream cellular responses (Mügge et al, 1991;Urbich et al, 2002;Zhang et al, 2001). The reaction between SO and NO is rapid, occurring at a rate of 6.7×10 9 M -1 s -1 , a near diffusion-limited rate (Huie and Padmajas, 1993).…”
Section: Discussionmentioning
confidence: 99%